Building Pathways for Future Learning with Japanese Lesson Study - Crystal Corle Loose (Adult Education Research Conference, 2014)
The purpose of this paper is to report on an qualitative action research study that was conducted in an elementary school in order to examine teacher perceptions of Japanese Lesson Study as a method of professional development.